2011
DOI: 10.1038/ncb2402
|View full text |Cite|
|
Sign up to set email alerts
|

p53 regulates epithelial–mesenchymal transition and stem cell properties through modulating miRNAs

Abstract: ZEB1 is a protein of 1124 amino acids with a predicted relative molecular mass ~124K. However, in Supplementary Fig. S5 (corresponding to Fig. 4a) of our manuscript, the uncropped image of the ZEB1 immunoblot shows two bands with a relative molecular mass of 200K and 125K, respectively. Two major ZEB1 signals (M r 124K and 200K) have been observed in western blots when using different antibodies in various cell types (please see references 1-4 below). Therefore, to examine whether the bands observed in our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(162 citation statements)
references
References 4 publications
11
150
0
1
Order By: Relevance
“…Collectively, these data highlight the importance of miR-200c overexpression and its epigenetic regulation in metastatic CRC, which may be an important initial step that triggers the MET phenotype which ensues after EMT-mediated emigration of these neoplastic clones of CRC cells to the liver. In addition, transactivation of the miR-200 family by p5329 and a feedback loop mechanism between miR-200 family members and ZEB1 have also been proposed 13 30 31. However, the methylation status of the miR-200c promoter region did not correlate with the p53 genotype in CRC cell lines analysed in our study (online supplementary figure 1).…”
Section: Discussionmentioning
confidence: 49%
“…Collectively, these data highlight the importance of miR-200c overexpression and its epigenetic regulation in metastatic CRC, which may be an important initial step that triggers the MET phenotype which ensues after EMT-mediated emigration of these neoplastic clones of CRC cells to the liver. In addition, transactivation of the miR-200 family by p5329 and a feedback loop mechanism between miR-200 family members and ZEB1 have also been proposed 13 30 31. However, the methylation status of the miR-200c promoter region did not correlate with the p53 genotype in CRC cell lines analysed in our study (online supplementary figure 1).…”
Section: Discussionmentioning
confidence: 49%
“…Wild-type p53 inhibits the EMT by direct transactivation of miR-200c, which targets ZEB1 mRNA for decay. Meanwhile, mutant p53 proteins induce an EMT 47. Accordingly, we found that si TP53 downregulated ZEB1 in SW480 cells (figure 6D).…”
Section: Resultsmentioning
confidence: 77%
“…Interestingly, wild-type and mutant p53 have been described to have opposite functions with regard to EMT 47. Wild-type p53 inhibits the EMT by direct transactivation of miR-200c, which targets ZEB1 mRNA for decay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-step process of metastasis includes local invasion, intravasation to the lymph and blood systems, survival in the bloodstream, extravasation from the microvessels and colonization at a secondary site (2,3). There is evidence to suggest that epithelial to mesenchymal transition (EMT) contributes to cancer progression, invasion and migration in various types of cancer (4,5). EMT is a cellular process during which epithelial polarized cells become motile mesenchymal-appearing cells (6).…”
Section: Introductionmentioning
confidence: 99%